2018
DOI: 10.1016/j.cegh.2017.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Low- level smoking among diabetes patients in India: a smoking cessation challenge

Abstract: Background: Little research in low and middle-income countries has been conducted on shifts in levels of smoking among those suffering from chronic diseases exposed to cessation messages. We present data on such shifts among diabetes patients participating in a randomized controlled cessation trial in Kerala state, India. The two-arm trial tested the relative effectiveness of diabetes specific cessation messages from doctors and the added value of motivational interviewing by trained cessation counsellors. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…As outlined in Table 1 , significant differences in smoking cessation between the intervention and control group were only reported in the studies by Canga et al 35 and Thankappan et al 31 at follow-up at 6 months, and in the studies by Pérez-Tortosa et al 32 and Thankappan et al 25 at follow-up at 1 year. Conversely, the other study authors 22 , 24 , 30 , 33 , 34 , 36 - 38 did not report a significant improvement in the smoking cessation rate of the intervention group when compared to the control group; and although Ng et al 38 reported a significant decrease in the self-reported smoking prevalence in both groups at follow-up at 6 months, in these studies the smoking abstinence rate in both the intervention and control group was also deemed to be insignificant. Given these inconsistent findings, and taking into consideration the high level of heterogeneity amongst the interventions of the studies, a narrative component analysis was conducted.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…As outlined in Table 1 , significant differences in smoking cessation between the intervention and control group were only reported in the studies by Canga et al 35 and Thankappan et al 31 at follow-up at 6 months, and in the studies by Pérez-Tortosa et al 32 and Thankappan et al 25 at follow-up at 1 year. Conversely, the other study authors 22 , 24 , 30 , 33 , 34 , 36 - 38 did not report a significant improvement in the smoking cessation rate of the intervention group when compared to the control group; and although Ng et al 38 reported a significant decrease in the self-reported smoking prevalence in both groups at follow-up at 6 months, in these studies the smoking abstinence rate in both the intervention and control group was also deemed to be insignificant. Given these inconsistent findings, and taking into consideration the high level of heterogeneity amongst the interventions of the studies, a narrative component analysis was conducted.…”
Section: Resultsmentioning
confidence: 86%
“…Both Lam et al 28 and Thankappan et al 29 published the findings from the randomized control trials by Li et al 30 and Thankappan et al 31 , respectively, in conference proceedings. Furthermore, in the publications by Thankappan et al 25 and Nichter et al 24 , the authors followed up participants from the Thankappan et al 31 trial for a total of one and two years, respectively, without providing any additional interventions. Additionally, Mini et al 23 reported on the biochemical verification of a sample of non-smokers who participated in the Thankappan et al 31 trail at follow-up at 1 year, in their publication.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 16 interventions which aimed to deliver TPE interventions using a personalized and individual approach [5,[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60]. All these interventions were focused on lifestyle and disease education and self-management techniques for diabetes except for four interventions which were primarily aimed at smoking cessation among patients with diabetes [48,50], personalized diabetes risk assessments during ophthalmologic visits [58] and improving physical activity [60].…”
Section: Individually Delivered Interventionsmentioning
confidence: 99%
“…Individually delivered interventions: There were 16 interventions which aimed to deliver TPE interventions using a personalized and individual approach [5,[44][45][46][47][48][49][50][51][52][53][54][55][56][57][58]. All these interventions were focused on lifestyle and disease education and self-management techniques for diabetes except four interventions which were primarily aimed for smoking cessation among patients with diabetes [46,48]; personalized diabetes risk assessments during ophthalmologic visits [56] and improving physical activity [58].…”
Section: Group Interventionsmentioning
confidence: 99%